2022
DOI: 10.3389/fnmol.2022.858582
|View full text |Cite
|
Sign up to set email alerts
|

AUTS2 Syndrome: Molecular Mechanisms and Model Systems

Abstract: AUTS2 syndrome is a genetic disorder that causes intellectual disability, microcephaly, and other phenotypes. Syndrome severity is worse when mutations involve 3’ regions (exons 9-19) of the AUTS2 gene. Human AUTS2 protein has two major isoforms, full-length (1259 aa) and C-terminal (711 aa), the latter produced from an alternative transcription start site in exon 9. Structurally, AUTS2 contains the putative “AUTS2 domain” (∼200 aa) conserved among AUTS2 and its ohnologs, fibrosin, and fibrosin-like-1. Also, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 109 publications
0
26
0
Order By: Relevance
“…It should, however, be noted that most species eventually lost one of the two copies, suggesting that a single copy of the gene is sufficient. When looking at the auts2 gene structure and predicted protein coding size and domains, we observed that in teleost fish (as highlighted here in medaka and zebrafish in Figure 4 ), the auts2a gene encodes for a long (1282 and 1278 amino acids in medaka and zebrafish, respectively) protein that is highly similar to the human AUTS2 protein [ 4 ]. The human gene is also known to encode many alternatively spliced variants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It should, however, be noted that most species eventually lost one of the two copies, suggesting that a single copy of the gene is sufficient. When looking at the auts2 gene structure and predicted protein coding size and domains, we observed that in teleost fish (as highlighted here in medaka and zebrafish in Figure 4 ), the auts2a gene encodes for a long (1282 and 1278 amino acids in medaka and zebrafish, respectively) protein that is highly similar to the human AUTS2 protein [ 4 ]. The human gene is also known to encode many alternatively spliced variants.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate conserved sequence features between species, amino acid sequences (accession numbers available in Tables S5 and S6 ) were aligned using the BioEdit software (version 7.0.5.3, Raleigh, NC, USA) and conserved domains were visually identified based on existing data [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations